Update of Arthropod Containment Guidelines. (June 2019) - Fontes, Benjamin
The American Society of Tropical Medicine and Hygiene's American Committee of Medical Entomology has released their updated edition (Version 3.2) of the Arthropod Containment Guidelines. The Guidelines were written to provide pertinent risk assessment and risk management information for the safe handling and rearing of arthropods used in research. The format of the Guidelines is like the outline used in the CDC/NIH Biosafety in Microbiological and Biomedical Laboratories. Four Arthropod Containment Levels (ACLs) are described, with increasing requirements for safety and security from ACL-1 to ACL-4. Each containment level provides information on standard practices, including standard and special practices, storage, labeling, monitoring and trapping escaped arthropods, training, medical surveillance, safety equipment, and facility design.